2017
DOI: 10.1177/0733464816687448
|View full text |Cite
|
Sign up to set email alerts
|

Active Interest Mentorship for Soon-to-Retire People: A Self-Sustaining Retirement Preparation Program

Abstract: Retirement is a major life transition that often leads to maladjustments and mental health hazards. In this study, we developed an innovative retirement preparation program, the Active Interest Mentorship Scheme (AIMS), which utilized active interest development as a positive entry point through which to engage soon-to-retire people. Each retiree received a 1-year mentorship 6 months before retirement. Adopting a quasi-experimental design, the study aimed to evaluate the efficacy of the AIMS in protecting reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
1
9
2
Order By: Relevance
“…This is in line with existing literature supporting the interest among medical professionals for late career mentorship and retirement planning [13]. Other professions have also recognized the benefits of retirement mentoring programs [16,17]. Wang et al [16] showed that mentoring corporate employees for 6 months before and after retirement improved their affect, self-esteem, and life satisfaction, as well as containing depression and anxiety.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is in line with existing literature supporting the interest among medical professionals for late career mentorship and retirement planning [13]. Other professions have also recognized the benefits of retirement mentoring programs [16,17]. Wang et al [16] showed that mentoring corporate employees for 6 months before and after retirement improved their affect, self-esteem, and life satisfaction, as well as containing depression and anxiety.…”
Section: Discussionsupporting
confidence: 79%
“…Other professions have also recognized the benefits of retirement mentoring programs [16,17]. Wang et al [16] showed that mentoring corporate employees for 6 months before and after retirement improved their affect, self-esteem, and life satisfaction, as well as containing depression and anxiety. Importantly, many retirees who had completed the 1-year mentorship program expressed interest in becoming retirement mentors themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, we included several individual-level characteristics in the analysis. The continuous variable of Age was limited in our sample in that only people over age 50 were included because they are verging on retirement (Ng et al, 2019). As we focused on individuals who had not reached the official retirement age, the age cohort was bounded by 50 and 67 (M = 55.78, SD = 3.54).…”
Section: Sample and Datamentioning
confidence: 99%
“…Retirement is one of the main transitional periods in every person's life. It often leads to imbalances in the psycho-emotional state and social situation (Siu-man et al, 2017). The social status changing due to retirement has an impact on the person's mental state, on changing his perception of society and relatives, transforming his role in life, reflects his financial situation and, subsequently, on health and adaptation to environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists around the world are exploring problems and ways to mitigate the transition period of retirement. In particular, they offer a mentoring program as a technology for preparing for retirement (Siu-man et al, 2017). Scientists also analyze biopsychosocial factors (resources, planning, retirement conditions, pension expectations) that affect life satisfaction (Siguaw et al, 2017).…”
Section: Introductionmentioning
confidence: 99%